Nutritional Issues in Children with Dysphagia. - Ortiz Pérez, Pilar; Valero-Arredondo, Inés; Torcuato-Rubio, Encarnación; Herrador-López, Marta; Martin‐Masot, Rafael; Navas-López, Víctor Manuel (MDPI, 2024)
(1) Background: Pediatric dysphagia presents significant nutritional challenges, often impacting growth and development due to reduced oral intake, increased nutritional needs, and gastrointestinal complications; (2) Methods: This prospective quasi-experimental study assessed 117 children under 14 years old (20 patients were under 1 year old, 80 were aged 1–7 years, and 17 were older than 7 years), diagnosed with swallowing disorders, to analyze their caloric, macro-, and micronutrient intake and identify potential deficiencies. The severity of dysphagia was established using functional oral intake scales, and dietary records were reviewed over a 3-day period; (3) Results: The study revealed that 39.8% of participants did not meet their total energy expenditure (TEE), highlighting a high prevalence of malnutrition among these children. Furthermore, patients using feeding devices exhibited a significantly lower caloric intake, and over half required significantly modified food textures. After individualized speech therapy and nutritional rehabilitation, partici- pants showed significant improvements in caloric intake, with their energy coverage increasing from 958% to 1198% of the daily requirement. Rehabilitation also improved tolerance to a broader range of food textures; (4) Conclusions: This research underscores the importance of multidisciplinary, individualized nutritional strategies to address the specific challenges of pediatric dysphagia, empha- sizing the role of enteral nutrition and therapeutic interventions in improving the quality of life and nutritional outcomes of these children. Further studies are recommended to assess the long-term impact of such strategies.
Keywords: Niños - Trastornos nutricionales; Nutrición; Deglutition disorders; Malnutrition; Dysphagia; Pediatric rehabilitation program